Proceso de migración realizado por los Shawi de Nuevo Chacatán, Loreto San Juan Bautista 2023 - Rodriguez Macuyama, Jhonatan Erik (2024)
The research "Migration process carried out by the shawi people of Nuevo Chacatán, Loreto San Juan Bautista 2023" was conducted at kilometer 72,780 of the Iquitos-Nauta highway. At San Juan Bautista district, at Maynas province, at Loreto department. Employing a qualitative approach and ethnographic design. Identifying 20 key informants and applying a snowball sampling strategy. Mainly, adults from the community were interviewed, as well as the main leader Wa'an Nahwiri Rafael Chanchari Pizuri, who is known as a nunentun, a shawi plant healer, an expert in healing methods through ayahuasca rituals. Simultaneously, data collection instruments were applied through semi-structured interviews and community information guides. The research shows that the new inhabitants of Chacatán have three motivations to migrate from Sillay to Nuevo Chacatán, the main ones being: a) accusations of practicing witchcraft, b) prior knowledge of a family member who settled there previously, and c) seeking treatment for some illness with traditional shawi medicine. The reproduction of their own institutions, values, and social organization is a form of ethnic resistance, present in the migratory process that reveals socio-cultural changes pressured by the capitalist system.